Eksperimen Pembelajaran Matematika Dengan Pendekatan Realistic Mathematic Education Dan Problem Based Learning Terhadap Hasil Belajar Siswa DitinjauDari Motivasi Belajar Pada Kelas XI IPASMA Muhammadiyah 1 KaranganyarTahun 2016/2017 - Fitriana, Dyah Ayu, Drs.Slamet HW, M. M., M. Pd (2017)
ABSTRACT Dyah Ayu Fitriana/ A410130144. EKSPERIMEN PEMBELAJARAN MATEMATIKA DENGAN PENDEKATAN REALISTIC MATHEMATIC EDUCATION DAN PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR SISWA DITINJAU DARI MOTIVASI BELAJAR PADA KELAS XI IPA SMA MUHAMMADIYAH 1 KARANGANYAR TAHUN 2016/2017. Skripsi. Program Studi Pendidikan Matematika, Fakultas Keguruan dan Imu Pendidikan, Universitas Muhammadiyah Surakarta. Desember, 2016 This research aims to know the: (1) influence the learning approach Realistic Mathematic Education and Problem Based Learning. (2) the influence of learning motivation towards learning outcomes. (3) the interaction between the learning approach Realistic Mathematic Education and Problem Based Learning in terms of learning motivation towards learning outcomes for mathematics. Types of quantitative research with the design of experiments. Sample research with Cluster Random Sampling from a population of grade XI IPA SMA Muhammadiyah Surakarta 1 2016/2017. Data collection techniques with techniques now, tests, and documentation. Prior to analysis, first performed a test of balance, a test of normality, and the test of its homogeneity. Data analysis techniques with an analysis of the variansi two way cell does not equal to 5% significance level. The results of this research were obtained: (1) there is the influence of learning approach against the results of the learning of mathematics. (2) there is the influence of motivation towards learning outcomes learning math. (3) there is no interaction between learning motivation and learning approach against the results of the learning of mathematics. Keyword: Realistic Mathematic Education. Problem Based Learning. Approach To Learning. Learning Motivation